Global Research Trends on Augmented Reality in Science Education: A Bibliometric Analysis (2020–2025) - Rahmia Tulljanah Rahmi; Wahyuni Mulia Helmi; Rahmatia Wulan Dari; Riri Marfilinda; Meria Ultra Gusteti (Postgraduate, University of Mataram, 2026)
This study uses a bibliometric approach to analyze global research trends regarding the use of Augmented Reality (AR) in science education in the period 2020–2025. Data was obtained from the Scopus database as of July 16, 2025 using the keywords